2010
DOI: 10.1007/s00125-010-1698-8
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-selective chelation improves function and antioxidant defences in cardiovascular tissues of rats as a model of diabetes: comparisons between triethylenetetramine and three less copper-selective transition-metal-targeted treatments

Abstract: Aims/hypothesis Treatment with the Cu(II)-selective chelator triethylenetetramine (TETA) improves cardiovascular disease in human patients, and cardiac and vascular/renal disease in rats used as a model of diabetes. Here we tested two hypotheses: first, that TETA elicits greater improvement in organ function than less Cu-selective transition-metal-targeted treatments; second, that the therapeutic actions of TETA are consistent with mediation through suppression of oxidative stress.Methods Rats were made diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…It is noteworthy that both SSAT2 and SSAT1 have been associated with the regulation of hypoxia-inducible factor 1␣, which functions as a master regulator of oxygen homeostasis (Vogel et al, 2006;Baek et al, 2007a,b). In a few comparative trials, TETA has exhibited enhanced activity compared with other common metal ch- (Yoshii et al, 2001;Yu et al, 2006;Lu et al, 2010a), which may be attributed to its higher copper chelation selectivity and potency compared with other tested chelators. However, the novel cellular targets of TETA are expected to explain the physiological background of its therapeutic potential in many diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that both SSAT2 and SSAT1 have been associated with the regulation of hypoxia-inducible factor 1␣, which functions as a master regulator of oxygen homeostasis (Vogel et al, 2006;Baek et al, 2007a,b). In a few comparative trials, TETA has exhibited enhanced activity compared with other common metal ch- (Yoshii et al, 2001;Yu et al, 2006;Lu et al, 2010a), which may be attributed to its higher copper chelation selectivity and potency compared with other tested chelators. However, the novel cellular targets of TETA are expected to explain the physiological background of its therapeutic potential in many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of type 2 diabetes, Zucker diabetic fatty rats treated with TETA demonstrated significantly reduced development of diabetic cardiomyopathy (Baynes and Murray, 2009). Although the exact mechanism of these beneficial effects is not known, Lu et al (2010a) suggested that copper chelation by TETA induces antioxidant defense mechanism, thus alleviating diabetes-associated complications. Kodama et al (1997) were the first to report that TETA is readily acetylated in humans into N 1 -monoacetyltriethylenetetramine (N 1 AcTETA; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover we can treat the diabetic patient with copper specific chelator, so that various complications of diabetes mellitus including diabetic nephropathy could be prevented as it has been proven beneficial in various animal models. [18,19,20,21,22] Our study could give new insight for understanding the risk factor for development of diabetic nephropathy and also therapeutic modality could be develop to remove excess of copper ions from the diabetic patient, so that overall management of diabetic patient improves by decreasing various complication associated with copper induce oxidative stress.…”
mentioning
confidence: 89%
“…TETA treatment reduces left ventricular hypertrophy in patients (7). It also improves left ventricular function (5,82), restores damaged aortic and left ventricular structures (5,83), and improves cardiac antioxidant defense (83)(84)(85) in rat models of diabetes. However, the exact target(s) and mechanism of actions of TETA in diabetic heart failure are still under investigation.…”
Section: Mechanism Of Action In Other Clinical Applicationsmentioning
confidence: 99%